Time Trend of the Radiation Exposure Dose in Endoscopic Retrograde Cholangiopancreatography Over an 8-Year Period: A Single-Center Retrospective Study. (14th January 2021) - Hayashi, Shiro; Nishida, Tsutomu; Osugi, Naoto; Yamaoka, Sho; Sugimoto, Aya; Mukai, Kaori; Nakamatsu, Dai; Matsumoto, Kengo; Yamamoto, Masashi; Fukui, Koji; Takenaka, Mamoru; Hosono, Makoto; et al.
Abstract : INTRODUCTION: The global needs for a reduction in radiation exposure (RE) are increasing. Endoscopic retrograde cholangiopancreatography (ERCP) is a significant fluoroscopic procedure in the gastrointestinal field. However, the actual RE in ERCP and its annual trend are still unclear. Therefore, we examined the yearly trend of RE in ERCP. METHODS: This retrospective, single-center cohort study included consecutive cases of ERCP from September 2012 to June 2019. We measured the air kerma (AK, mGy), dose area product (DAP, Gycm 2 ), and fluoroscopy time (FT, min). We also evaluated the annual trend of the RE before and after the fluoroscopy device update. RESULTS: In total, 2, 174 patients receiving ERCP were enrolled. Among these, the mean age was 74.3 years, and 913 patients were women (42.0%). The median/third quartile values of AK (mGy), DAP (Gycm 2 ), and FT (min) were 109/234 mGy, 13.3/25.8 Gycm 2, and 18.2/27.7 minutes. The annual AK, DAP, and FT from 2012 to 2019 were 138, 207, 173, 177, 106, 71.0, 45.0, and 33.3 mGy; 23, 21.4, 19, 18.3, 11.9, 9.0, 6.8, and 6.4 Gycm 2 ; and 12.5, 12.1, 9.7, 9.8, 8.2, 10.8, 9.4, and 10.3 minutes, respectively. The corresponding values before and after the update in July 2016 were 177 and 52 mGy ( P < 0.0001), 19.2 and 7.6 Gycm 2 ( P < 0.0001), and 10.2, and 9.9 minutes ( P = 0.05), respectively. DISCUSSION: The RE from ERCP tended to decrease every year, especially after fluoroscopy device updates.